Use of the dapivirine vaginal ring and effect on cervical cytology abnormalities. (15th March 2020) - Reddy, Krishnaveni; Kelly, Cliff; Brown, Elizabeth R.; Jeenarain, Nitesha; Naidoo, Logashvari; Siva, Samantha; Bekker, Linda-Gail; Nair, Gonasagrie; Makanani, Bonus; Chinula, Lameck; Mgodi, Nyaradzo; Chirenje, Zvavahera; et al.
Abstract : Objective: We aimed to determine if the dapivirine vaginal ring and the ring device alone (flexible silicone matrix polymer) was associated with the development of cervical cytology abnormalities. Design: Secondary analysis comparing cervical cytology results between two randomized controlled microbicide trials (MTN-020/ASPIRE and MTN-003/VOICE). Methods: Data from ASPIRE, a phase III, placebo-controlled trial of the dapivirine vaginal ring, were used in this analysis. Cervical cytology smears were evaluated at baseline and at the final visit with product use. We compared cytology results between women randomized to dapivirine versus placebo vaginal ring. We further assessed for the effect of the vaginal ring device on cervical cytology by comparing results with data from the oral placebo arm of VOICE, a prior HIV-1 prevention trial conducted in a similar population. Results: Cervical cytology results for 2394 women from ASPIRE (1197 per study arm) were used in this analysis; median time between baseline and final visit with product use was 22.1 months. Cytology smear findings were comparable between dapivirine and placebo vaginal ring arms: at final visit, normal: 90.6 versus 91.5%, ASC-US//LSIL: 7.8 versus 7.4%, ASC-H/HSIL/AGC/AGC-favor neoplastic: 1.7 versus 1.1%, P  = 0.44. Cytology data from VOICE had findings (normal: 87.8%, ASC-US/LSIL: 9.8%, ASC-H/HSIL/AGC/AGC-favor neoplastic: 2.4%) comparable with that of both dapivirine ( P  = 0.93) and placebo vaginal ring arms ( P  = 0.24). Conclusion: These findings indicate that neither use of the dapivirine vaginal ring nor the vaginal ring device alone, over a period of 2 years, is associated with development of cervical cytology abnormalities that could lead to precancerous or cancerous lesions.